Meta-requirement mapping model - Muhamad Idaham, Umar Ong; M. A., Ameedeen (IOP Publishing, 2020)
The challenges faced by software vendor in competing for tenders in todays are massive and are desperately in need of intervention by the kind people of the research community. With very small resources available at their disposal, it is a daunting task them in the pursue to gain new software development projects each time new tenders are coming out. The objective of this publication is to propose an initial model that utilizes meta-requirement as a medium to validate the User Requirement Specification document that is included in the RFT. Looking forward, an algorithm will be developed for realizing the associations that was define in the propose model.